Inspiring climate-intentional business models: A repository of impact pathways for agribusinesses - Friedrich, Hannah; Nowak, Andreea C. (2025)
The Impact Pathway Reference Tool is a structured knowledge system that transforms diverse agribusiness experiences into actionable insights for designing climate-intentional business models. By linking business activities to measurable outcomes and impacts, it enables agribusinesses to collect evidence on effective practices, identify gaps, and align with resilience and sustainability goals. Its core strength lies in converting real-world company experiences into ready-to-use templates that support innovation design, investment planning, and impact tracking.